2009
DOI: 10.2320/matertrans.mra2008266
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Reactive Diffusion between Sn and Electroless Ni–P at 473 K

Abstract: Nickel-phosphorus alloys are electrolessly deposited onto Cu-base conductors to suppress formation of Cu-Sn compounds during soldering using Sn-base solders. However, a Ni-Sn compound is produced during soldering, and continuously grows during energization heating at solid-state temperatures. To examine influence of P on the growth behavior of the Ni-Sn compound during energization heating, the kinetics of the solid-state reactive diffusion between Sn and electroless Ni-P alloys was experimentally determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The second intermetallic phase, possible to detect only in Ni-4.3P samples after reaction with solder, was described as (Ni,Cu) 3 Sn 4 . These results are in agreement with the examination of Yoon et al, [17] who identified the same intermetallics at the Sn-0.4Cu/ENIG interface and also observed similar morphology of large and faced scallops, but after 60 minutes of reaction time at 528 K. On the other 10-14 -225 ± 20 [14] 0 289 (Ea of self-diffusion in pure Ni) [14] hand, the second intermetallic phase (Ni,Cu) 3 Sn 4 formation was reported [2,18] during solid state reaction of plating and pure Sn solder. The presented here experimental results allow the conclusion that larger amount of phosphorous within the applied plating retarded the growth of (Cu,Ni) 6 Sn 5 and also the formation of Ni 3 Sn 4 intermetallic phases.…”
Section: Ni-p/sac Interactionmentioning
confidence: 76%
“…The second intermetallic phase, possible to detect only in Ni-4.3P samples after reaction with solder, was described as (Ni,Cu) 3 Sn 4 . These results are in agreement with the examination of Yoon et al, [17] who identified the same intermetallics at the Sn-0.4Cu/ENIG interface and also observed similar morphology of large and faced scallops, but after 60 minutes of reaction time at 528 K. On the other 10-14 -225 ± 20 [14] 0 289 (Ea of self-diffusion in pure Ni) [14] hand, the second intermetallic phase (Ni,Cu) 3 Sn 4 formation was reported [2,18] during solid state reaction of plating and pure Sn solder. The presented here experimental results allow the conclusion that larger amount of phosphorous within the applied plating retarded the growth of (Cu,Ni) 6 Sn 5 and also the formation of Ni 3 Sn 4 intermetallic phases.…”
Section: Ni-p/sac Interactionmentioning
confidence: 76%
“…Table II lists the values of the lattice mismatch and the surface energy parameters of the Ni(P) film over various UBM materials using the material data found in the literature. [26,27] It can be seen that the utilized UBM materials fall into two distinct groups: noble metals Cu, Ag, and Au vs Ni and Co. The former substrates had relatively larger lattice mismatches with the Ni(P) film than the latter, and the former exhibited negative surface energy parameters, while the latter had significantly smaller lattice mismatches and positive energy parameters.…”
Section: B Effects Of Ag Au Ni and Co Ubmsmentioning
confidence: 96%
“…A qualitative understanding of the critical cluster size, in this case critical size of abnormally large nodules, can be constructed as follows in the manner of Tu et al [25] The free energy change of the The lattice parameters of the Ni(5P) film were deduced from Yamakami and Kajihara, [26] and the surface energies of metals reported by Skriver and Rosengard [27] were used. [27] exhibiting the regions of the three major growth modes.…”
Section: B Effects Of Ag Au Ni and Co Ubmsmentioning
confidence: 99%
“…It requires a combination of different characterization techniques. An illustration of this complexity are contradictory results, even obtained by using the best structure characterization techniques such as XRD and EXAFS -the dependence of the lattice parameter in the fcc phase of Ni-P on P content is opposite in alloys produced by different techniques [2], [11], [12]. In this regard, a more plausible approach at the initial stages of the research is to study the structure and properties of Ni-P coatings, depending on the basic parameter of electroless deposition i.e.…”
Section: Introductionmentioning
confidence: 99%